Macht, onmacht en volmacht in 1 Timoteüs 2:8−15 - Houwelingen, P. H. Rob van (HTS teologiese studies, 2012)
Power, powerlessness and authorised power in 1 Timothy 2:8−15.Thinking in terms of ecclesiastical power has often found a breeding ground in the Pastoral Epistles. To what extent is this justified? This article will examine a passage that always comes up when the position of women in the church is discussed: 1 Timothy 2:8−15. Consecutively, three aspects will be considered: power, powerlessness and authorised power. Power says something about the underlying problem that Timothy faced: the male or female relationships in the church of Ephesus threatened to degenerate into a power struggle. Powerlessness refers to the story of Adam and Eve referred to in verses 13−15. Its focus is the woman, Eve. The book of Genesis tells the story of human weakness, which becomes in the first letter to Timothy a sort of triptych about Eve and the Creation, Eve and the Fall and Eve and the Redemption. Authorised power is the way Paul tries to regulate the problematic situation in the congregation with apostolic rules. Not only because he wants something (βούλομαι) or because he does not allow something (οὐκ ἐπιτρέπω) , but also in particular to create space for the faithful Word.